Cultural Impacts on KM in the 21st Century. - Stankosky, Michael (VINE: Volume 40, Edition 3 & 4., 2010)
This VINE e-book is to provide an additional resource to knowing and understanding cultures, both across the world, and in organizational settings within the same country or region. The authors hail from a variety of backgrounds and work experiences themselves. The common denominator is their intense involvement in the knowledge management arena, trying to develop principles and practices to leverage knowledge assets under their cognizance. The guest editors' wish is that the reader will take away a better appreciation of humankind, and how we all attempt to live and function in a shared world.